Raman and his effect - Venkataraman, G. (Hyderabad, Universities Press (India) Limited, 1995)
This book deals with the famous Scattering Effect discovered by Sir C.V. Raman. It gives us deep insights into the character of this famous scientist and vividly describes the circumstances surrounding the discovery.
Bibliography p96; Index 97-99p.
Keywords: Physics